Health among lifetime victimized men - Soares, Joaquim; Macassa, Gloria; Miranda, Jamilette; Viitasara, Eija (Mittuniversitetet, Institutionen för hälsovetenskap, 2007)
Objectives. We examined differences in demographics/socio-economics, lifestyles and mental/ physical health between victimized/non-victimized men, and identified/quantified factors associated with mental/physical health. Study design. The study design was cross-sectional. Methods. The men were assessed in various areas (e.g., depression) by means of a questionnaire. Results. The univariate analyses showed that victims compared with non-victims were younger. They also had higher intermediate education levels, were more often blue-collar/low white-collar workers, were on student allowances and financially strained, smoked more, had a lower BMI, and reported headaches, depression, tension and cognitive difficulties more frequently. The regression analyses showed that financial strain rather than violence was a more important factor for illhealth. Only headaches and cognitive difficulties were associated with violence. Conclusions. Quite an number of men were in a poor physical/mental state, but there were few differences between victims/non-victims. Financial strain was determined to be a more important factor for ill-health than violence. Our data indicate that violence had little effect on men’s health. Our findings do not generally support a relationship between poor health and the abuse of men.